Total quality management and knowledge management in Malaysian manufacturing and service firms : a structural equation modeling approach / Ooi Keng Boon - Ooi, Keng Boon (2013)
This thesis purports to empirically investigate the multidimensionality of total quality management (TQM) and its association with knowledge management (KM) as perceived by the middle to higher level managers (i.e. executives, managers, senior managers, managing directors and chief executive officers (CEOs)) in the manufacturing and service firms in Malaysia. Based on a thorough review of existing literature, six dimensions of TQM (i.e. leadership, strategic planning, customer focus, human resource management, process management and information and analysis) grounded in Malcolm Baldrige National Quality Award (MBNQA) criteria and three components of KM (i.e. knowledge acquisition, knowledge distribution and knowledge application) were identified. A total of 203 usable surveys were collected from the manufacturing and service sectors that are planning for or have obtained the ISO 9001:2000 certification. They comprised of small, medium and large Malaysian firms. Structural Equation Modeling (SEM) technique was used to test the theoretical framework. The findings of this study proposed that four dimensions of TQM are instrumental for firms to increase their efficiency in KM. They are strategic planning, human resource management, systematic process management, as well as possessing an adequate level of information and analysis, in which strategic planning is the most significant determinant for KM in both manufacturing and service firms thus filling the literature gap of TQM and KM. However, leadership and customer focus were found to have no significant relationship to KM in both the sectors surveyed. Result of this cross sectional study also reveals insignificant difference with respect to the modeling of TQM‟s constructs validity between the two sectors. In other words, the chosen TQM practices in this study are equally applicable across both sectors. Furthermore, there also lies no significant difference in the relationship between TQM practices and the level of KM between both these sectors. One of the research limitations would be that the self-reported survey might include some biased response from the target respondents and this may pose as a major concern when verifying the pervasiveness or apparentness of the respondents towards TQM practices on KM. Nevertheless, the research creates awareness among the middle to higher level managers to focus on the six MBNQA dimensions that can help attain a superior KM. In terms of originality, this research examines the effect of six TQM practices on KM as well as presents a comparative analysis on TQM practices and KM between the two sectors from the perspective of both descriptive and structural relationships. Specifically, the construct validity and criterion validity with regards to the TQM practices is further confirmed in this thesis. Practically, this research can be used by middle to higher level managers from both the manufacturing and service side to evaluate the effectiveness of TQM practices on KM in their companies. They can focus their efforts on practices that show the most promising result for the establishment of competitive KM capabilities, by developing a deeper comprehension of the association between TQM practices and KM.